NATIONAL TRENDS IN THE PREVALENCE OF DISEASES AMONG RESIDENTS OF UKRAINE AND KHARKIV REGION - M.M. Mishchenko (Клінічна та профілактична медицина, 2022)
Introduction: the relevance of determining national trends in prevalence of diseases among the adult population in Ukraine is high, as it solves several important medical, social and economic problems of society.